The effects of competition and the presence of an audience on weight lifting performance - Rhea, M. R.; Landers, D. M.; Alvar, B. A.; Arent, S. M. (The Journal of Strength and Conditioning Research, 2003)
The purpose of this investigation was to examine the effects of the presence of an audience and competition on maximal weight lifting performance. Thirty-two recreationally trained participants (15 men, 17 women; 21 ± 2.5 years) performed a 1 repetition maximum (1RM) bench press during 3 different situations (coaction, competitive coaction, and audience condition). Subjects also completed the Activation-Deactivation Adjective Checklist Short Form following the 3 trials to measure arousal state during each of the 3 trials. Significant differences (p < 0.05) were found between competitive coaction and coaction trials as well as between audience and coaction trials. Both men and women demonstrated the highest performance in front of an audience (105 ± 48 kg) followed by competition (103 ± 46 kg) and then the coaction trial (93 ± 43 kg). No significant difference in arousal was measured between trials. The data suggest that performing a maximal lift in the presence of an audience or in competition facilitates performance and support the self-presentation and self-awareness theories. Social facilitation effects should be controlled in research settings and may aid the performance of weight lifting activities during events or competition.